Serous Ovarian Carcinoma Recurring as Malignant Mixed Mullerian Tumor - Demir Hale; Demiroz Ahu Senem; Aydin Ovgu; Erenel Hakan; Ilvan Sennur; Calay Zerrin; Demirkiran Fuat (Case Reports in Obstetrics and Gynecology)
Only five cases of recurrence of malignant mixed Mullerian tumor (carcinosarcoma) from the ovarian carcinoma have been published in the literature to our knowledge. A 64-year-old woman first underwent a total abdominal hysterectomy and bilateral salpingo-oophorectomy because of pelvic mass. Histological diagnosis was serous papillary carcinoma of the left ovary. After six courses of chemotherapy, CA125 level returned to normal range. However, she had persistent multiple mediastinal and para-aortic lymphadenopathies in spite of additional six courses of chemotherapy. Then she underwent the second operation about 2 years after primary surgery. Multiple excisional biopsies were taken from subcutaneous tissue, over the bowels and the left external iliac artery. The histopathological diagnosis which was confirmed by immunohistochemical study was malignant mixed Mullerian tumor for all metastatic foci. A rare case of ovarian serous papillary carcinoma recurring as malignant mixed Mullerian tumor is reported.